Integrative oncogenomic approaches for accelerated cancer-gene discovery - Zender, Lars (2008)
PURPOSE OF REVIEW: The completion of the human genome project has enabled several new technologies for studying cancer genetics and cancer genomes. However, genomic instability and heterogeneity of human tumors impedes a straightforward cataloging of cancer genes and possible therapeutic targets. Strategies enabling the distinction of causal genetic alterations from bystander genomic noise are needed and should significantly speed up the process of cancer-gene discovery. RECENT FINDINGS: A series of recent papers described the development of integrative oncogenomic approaches based on innovative cancer mouse models and how these can be used to speed up the discovery of new cancer genes. In the presented studies, spontaneously acquired genetic alterations in mouse tumors of defined genetic origin are used to filter/prioritize relevant lesions from complex human cancer genomes. As will be discussed in this review, a great advantage of this approach is that pinpointed candidate genes can be functionally validated in the right genetic context in vivo, which significantly increases confidence for later therapeutic development efforts. SUMMARY: The discussed approaches hold great promise to speed up the process of cancer-gene discovery and should be considered to complement time-consuming and costly endeavors like the Cancer Genome Project.